Reestablishing the Function and Esthetics in Traumatized Permanent Teeth with Large Apical Lesion - Alexandra Rubin Cocco; Ângelo Niemczewski Bobrowski; Rudimar Antônio Baldissera; Luiz Fernando Machado Silveira; Josué Martos (Case Reports in Dentistry)
Dental trauma is a challenge for dental integrity and can lead to pulp necrosis. The clinical case reports the diagnosis of a maxillary right central incisor traumatized and its multidisciplinary treatment. Calcium hydroxide material was used to perform the processing apexification. An apical surgery was carried out to remove the apical periodontitis and to return the aesthetics to the patient; internal and external tooth whitening in maxillary right central incisor was performed. We conclude that surgery associated with the root filling in the central incisor led to a successful completion. Moreover, it is of utmost importance to demonstrate the interaction between the various areas of dentistry.